TELİF HAKKINA DAYALI MARKA TESCİL İTİRAZI - (:unkn) unknown (My University, 2019)
Bir eser veya onun parçaları marka olarak tescil ettirilip, kullanıla-bilir. Böylece hem eserin değerlendirilebileceği ticari mecralar artırıl-makta hem de eserin telif hukuku korumasına ek olarak marka hukuku hükümlerince de korunması sağlanmaktadır. Eseri veya eser parçalarını marka olarak tescil ettirme veya üçüncü kişiler tarafından yapılacak baş-vurulara itiraz etme yetkisi telif hakkı sahibine aittir. Telif hakkı sahibi kendi izni olmadan yapılan başvurular karşısında 6769 sayılı Sınai Mül-kiyet Kanunu m.6/6’ya dayanarak itirazda bulunabilir.

A work or parts of it can be registered and used as a trademark. This registration enhances the scope of the commercial channels in which the work can be used. It also provides trademark holder with the protection based on trademark law provisions in addition to the protec-tion of copyright law. The copyright owner has the authority to register the work or parts of work as a trademark or to object to trademark re-gistration applications made by third parties. He may object to the applications made without his permission, based on the article 6/6 of the Industrial Property Code numbered 6769.